Caroline Arnould-Béhar and Véronique Vassal (eds), Art et archéologie du Proche-Orient hellénistique et romain. Les circulations artistiques entre Orient et Occident. Volume 1 & 2 - Erskine, Andrew (Journal of Greek Archaeology, 2021)
In May 2017 Caroline Arnould-Béhar and Véronique Vassal held a one-day workshop on the art and archaeology of the Hellenistic and Roman Near East at the Catholic University of Paris. They followed this up with a second workshop a year later. The proceedings of the meetings are published in these two volumes, eleven papers in the first and twelve in the second. The object of the workshops was to explore the interaction between the East and West through an examination of the material culture of the Hellenistic and Roman Near East with a particular focus on forms of artistic expression. The topics covered include, among other things, funerary monuments, town-planning, architecture, sculpture, painting, and mosaics.